Urban-Rural Disparity in Cancer Incidence, Mortality, and Survivals in Shanghai, China, During 2002 and 2015 - Li, Xiaopan; Deng, Yang; Tang, Weina; Sun, Qiao; Chen, Yichen; Yang, Chen; Yan, Bei; Wang, Yingying; Wang, Jing; Wang, Shuo; Yang, Fan; Ding, Yibo; et al. (Frontiers in Oncology, 2018)
Introduction: Disparities in the incidence, mortality, and survival of cancer types between urban and rural areas in China reflect the effects of different risk factor exposure, education, and different medical availability. We aimed to characterize the disparities in the incidence, mortality, and survivals of cancer types between urban and rural areasin Shanghai, China, 2002-2015. Materials and methods: The incidence and mortality were standardized by Segi’s world standard population. Trends in the incidence and mortality of cancers were compared using annual percent change. The five-year observed and relative survivals were calculated with life table and EdererII methods. Results: Age-standardized incidences and mortalities were 212.55/105 and 109.45/105 in urban areas and 209.78/105 and 103.99/105 in rural areas, respectively. Female breast cancer and colorectal cancer occurred more frequently in urban than in rural areas, quite in contrast to liver cancer and cervical cancer. Cancers of lung& bronchus, liver, stomach, and colon &rectum were the leading causes of cancer death in both areas. Age-standardized incidence of female breast cancer and colorectal cancer in urban areas increased while gastric cancer and liver cancer decreased in both areas. Age-standardized mortalities of cancers of breast, esophagus,stomach, colon & rectum, liver, and lung & bronchus decreased in both areas. For all cancers combined, the five-year observed and relative survivals of cancer patients were higher in urban than in rural areas. The five-year observed and relative survivals of cancers of liver, pancreas, stomach, brain &central nervous system, and prostate were higher in urban than in rural areas.The five-year observed and relative survivals of cervical cancer were higher in rural than in urban areas. Conclusions: Factors promoting female breast cancer and colorectal cancer in urban areas and liver cancer and cervical cancer in rural areas should be specifically intervenedincancer prophylaxis. Improved medical services can greatly prolong the survival of major cancersin rural areas.